Verifying high quality: Entry for sale - Pehr-Johan Norbäck; Lars Persson; Roger Svensson (Research Institute of Industrial Economics (IFN), 2017)
When and how do entrepreneurs sell their inventions? To address this issue, we develop an endogenous entry-sale asymmetric information oligopoly model. We show that lowquality inventions are sold directly or used for own entry. Inventors who sell post-entry use entry to credibly reveal information on quality. Incumbents are then willing to pay high prices for high-quality inventions to preempt rivals from obtaining them. Using Swedish data on patents granted to small firms and individuals, we find evidence that high-quality inventions are sold under preemptive bidding competition, post entry.
Keywords: G24; L1; L2; M13; O3; 330; Acquisitions; Innovation; Start-ups; Ownership; Patents; Verification; Quality